If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 84 + -3x = 45 Solving 84 + -3x = 45 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-84' to each side of the equation. 84 + -84 + -3x = 45 + -84 Combine like terms: 84 + -84 = 0 0 + -3x = 45 + -84 -3x = 45 + -84 Combine like terms: 45 + -84 = -39 -3x = -39 Divide each side by '-3'. x = 13 Simplifying x = 13
| F=1.8*60+32 | | -35z+56=20 | | 3y-5x=10 | | 1/2=-3-x | | 4z-5i=10-z | | Logx(9)=1.7 | | y=2px+x^2p^4 | | x^3+3x^2-2a+5=0 | | 1y-13=39 | | 3y-3=y+27 | | -x+5x=-8 | | 3(4-3s)=20 | | 9m=8m+90 | | =2-[(-2)+2]-2 | | y=lg(2x-5) | | y=log(2x-5) | | 6x-3=6x-9 | | 64k^2-32k=0 | | 31-3b=28b+63 | | 3.2+(-7.8)= | | 2a+3b=88 | | 3x^2+11x+20=0 | | (-3.9)+7.1= | | 7tan(30)=x | | 15(42x+40)=15(-8x+244) | | y+8=3(x+2)2 | | 12n=6n+7 | | 0.4+3.4= | | 3x-1+3x=-7+6x+6 | | 5x-2+2x=-8+7x+6 | | -3=7(y=9/7) | | -3=7(y=9/7 |